Sistem Informasi Rekam Medis Pada Puskesmas Dengan Menerapkan Algoritma K-Means Berbasis Web - Nasution, Fitri Handayani; Kurniawan, Rakhmat; Putri, Raissa Ramanda (Teknik Informatika Fakultas Ilmu Komputer, 2025)
Medical record management at Puskesmas is one of the important aspects in efficient health services. However, the manual system that is still widely used often causes various problems such as recording errors, and the slow process of making medical decisions. this study aims to design and build a web-based medical record information system that can facilitate digital patient data management. This system is also equipped with the application of the K-Means algorithm to categorize the types of diseases suffered by patients. The patient's disease will be categorized into 3 categories, namely very severe, severe, and not severe by the system. The system development method used is the waterfall method and Unified Modeling Language tools and the system development process using the PHP programming language and MySQL database. With this information system, it is hoped that it can facilitate medical record officers in recapitulating patient data and providing good service.